Avoidant/resistant rather than tolerant olive rootstocks are more effective in controlling Verticillium wilt - Díaz-Rueda, Pablo; Peinado-Torrubia, Procopio; Durán-Gutiérrez, Francisco J.; Alcántara-Romano, Pilar; Aguado, Ana; Capote, Nieves; Colmenero-Flores, José M. (Frontiers in Plant Science, 2022)
The identification of rootstocks of low susceptibility to Verticillium dahliae can become a valuable procedure to achieve effective control of Verticillium wilt in the olive grove. This not only involves the identification of suitable genotypes, but also the study of the interaction between the rootstock and the grafted scion. Thus, a rootstock that prevents or minimizes V. dahliae proliferation (avoidance/resistance strategy) can have very different effects on a susceptible scion compared to a rootstock that shows few or no symptoms despite being infected (tolerance strategy). Both resistance and tolerance mechanisms have been recently identified in wild olive genotypes with low susceptibility to V. dahliae. When used as rootstocks of the highly susceptible variety ‘Picual’, we found that resistant genotypes, including the cultivar ‘Frantoio’, were more effective than tolerant genotypes in controlling Verticillium wilt. Furthermore, tolerant genotypes were as ineffective as susceptible or extremely susceptible genotypes in controlling Verticillium wilt. We also identified rootstock-scion combinations with behaviours that were not expected according to the degree of susceptibility previously observed in the non-grafted rootstock. Although the rootstocks were able to control Verticillium wilt according to its degree of susceptibility to V. dahliae, the ability to control the infection was not adequately transferred to the grafted scion. Our results confirmed that: the degree of susceptibility to Verticillium wilt of an olive variety does not predict its performance as a rootstock; to use a very low susceptible genotype as rootstock of a susceptible scion increases the susceptibility of the genotype used as rootstock; in any case, avoidant/resistant rootstocks are more effective than tolerant rootstocks in reducing the susceptibility of the grafted plant to V. dahliae.